Effective communication during disasters making use of technology, media, and human resources - Kapur, Girish Bobby; Dyal, Jonathan; Bezek, Sarah (Waretown, New Jersey Apple Academic Press, 2017)
Effective Communication During Disasters: Making Use of Technology, Media, and Human Resources is an informative, multi-faceted resource on preparedness planning for effective communication before, during, and after a disaster occurs.
Introduction -- 1 Preparing for effective communications during disasters : lessons from a world health organization quality improvement project -- 2 Information dissemination analysis of different media towards the application for disaster pre-warning -- 3 The effectiveness of disaster risk communication : a systematic review of intervention studies -- 4 Near-real-time analysis of publicly communicated disaster response information -- 5 The future of social media use during emergencies in Australia : insights from the 2014 Australian and New Zealand disaster and emergency management conference social media workshop -- 6 Resilient disaster network based on software defined cognitive wireless network technology -- 7 Web 2.0 and internet social networking : a new tool for disaster management? lessons from Taiwan -- 8 Global health and natural disaster alerts : preparing mobile phones to endure the unthinkable -- 9 What it takes to get passed on : message content, style, and structure as predictors of retransmission in the Boston marathon bombing response -- 10 Leveraging public health nurses for disaster risk communication in Fukushima city: a qualitative analysis of nurses' written records of parenting counseling and peer discussions -- 11 Communication, perception, and behaviour during a natural disaster involving a "do not drink" and -- A subsequent "boil water" notice : a postal questionnaire study -- Index
Includes bibliographical references and index
Keywords: Emergency management; Emergency communication systems